Patient participation in shared decision-making in palliative care - an integrative review - Kuosmanen Lotta; Hupli Maija; Ahtiluoto Satu; Haavisto Elina (WILEY, 2022)
Background Shared decision-making is a process where the decisions regarding patients' care are done in collaboration with the patient, the patient's family and a healthcare professional or an interdisciplinary team. Shared decision-making is considered to be a part of patient centred care, and it enables patient autonomy which is a cornerstone of palliative care. In the past, research on the experiences of palliative care patients' participation in shared decision-making involving a nurse has been limited as the focus has mainly been on specific medical interventions, rather than holistic palliative care.Objectives To synthesise research findings on patient participation in shared decision-making in palliative care.Research design An integrative literature review.Methods The literature search was conducted by searching computerised databases (CINAHL, PubMed, PsychINFO and COCHRANE). The search resulted in 12 articles. The quality of the included articles was evaluated with JBI checklist, and the data analysis was done using inductive content analysis. Reporting was done according to a PRISMA checklist.Findings Patients do participate in shared decision-making and desire to participate in everyday nursing care decisions, treatment-related medical decisions and end-of-life decisions. The prerequisites for patient participation in shared decision-making are interdisciplinary teamwork, open communication, good patient-healthcare professional relationship, a favourable environment and mutual information.Conclusion Palliative care patients do participate and desire to participate in decisions that cover a much broader range of topics than just medical interventions and this should be addressed in future research and in practise. The main responsibility for successful patient participation in shared decision-making lies with the healthcare professionals and the organisations providing palliative care. There is a need to conduct more research from the patient's perspective and explore the meaning of participating in shared decision-making from the patient's point of view.